2012
DOI: 10.1007/s11670-012-0196-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CAII expression in gastric cancer: Correlation with invasion and metastasis

Abstract: Objective: Human carbonic anhydrases II (CAII) gene plays an important role in different cancer. However, its relevance to gastric cancer (GC) remains unclear. In the present study, we aimed to investigate the expression of CAII in GC and explore its correlation with some clinicopathologic characteristics of GC.Methods: The expression of CAII in 20 specimens of normal gastric mucosa, 38 specimens of intraepithelial neoplasia and 112 specimens of gastric carcinoma were detected by immunohistochemical techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Proteomics analysis identified CA2 as a potential biomarker, which exerted significant inhibitory effects on cell growth in CRC ( 23 ). CA2 expression was also associated with lymph node metastasis in gastric cancer, and a previous study reported that its reduction may contribute to tumor metastasis ( 24 ). Therefore, CA2 may also be used as a therapeutical target for metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…Proteomics analysis identified CA2 as a potential biomarker, which exerted significant inhibitory effects on cell growth in CRC ( 23 ). CA2 expression was also associated with lymph node metastasis in gastric cancer, and a previous study reported that its reduction may contribute to tumor metastasis ( 24 ). Therefore, CA2 may also be used as a therapeutical target for metastasis.…”
Section: Discussionmentioning
confidence: 90%
“…Carbonic anhydrase II (hCAII) has important function in physiology and pathology process. CA II highly expresses in different normal organs, but its expression is inhibited in cancer cells (Li, Xie et al, ; Sheng, Dong, Zhou, Li, & Dong, ). CA II is also associated with osteopetrosis and renal tubular acidosis (Borthwick et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of CAII was significantly associated with metastatic disease, although there was no association with survival. In gastric cancer, low CAII expression correlates with tumor size, distant metastasis, TNM-stage, and poorer overall survival [16,37]. In addition, expression of CAII has been reported significantly downregulated in metastatic gastric cancer cells [38].…”
Section: Discussionmentioning
confidence: 99%